Rapid Prototyping Theory and Practice - Kamrani, Ali K.; Nasr, Emad Abouel (Manufacturing Systems Engineering Series, 2006)
Rapid prototyping techniques have been increasingly used by industry to reduce product development cycles. A large number of processes have been developed allowing the use of various materials ranging from plastics to metal for the development of prototypes. Rapid Prototyping: Theory and Practice provides a comprehensive collection of the latest research and technical work in the field with an emphasis on both rapid tooling and rapid manufacturing. Drawing upon the collective knowledge of renowned experts in the industrial engineering field, Ali Kamrani and Emad Abouel Nasr have assembled a wide ranging treatise on rapid prototyping that includes: Up to date documentation on the current scope of research on rapid prototyping, tooling and manufacturing. Methodologies and technologies to support a customer-focussed and mass customization approach to production. Detailed analysis and case studies of the application of rapid prototyping, rapid tooling and rapid manufacturing in fields such as medical and biomedical manufacturing, aerospace industry and automotive industry.